Contemporary Art in Nairobi’s Nightlife: Creating hyperreal worlds on Lang’ata road - Mbogo, Fredrick (PARALAXE, 2019)
Nairobi’s nightlife comes loaded with an array of suggestions, through created spectacle, about how interaction should take place. This paper is interested in how elements of design in some of Nairobi’s nightclubs define the kind of performance expected of a client within its premises. It focuses on clubs along Nairobi’s Lang’ata road. These clubs, the paper claims, are aware of the kinds of clients whose tastes they hope to successfully provide. At the heart of everything, the ambiance created through the design adapted defines the kind of client. This means that clients are expected to take up roles and perform some kind of identity while within these spaces. On the one hand there are clubs that sell themselves as spaces for sports enthusiasts, others as providers of wild-game experiences with inviting catch phrases as “meet the big five” on their menu, still others will sell themselves as purveyors of urban identity and others as carving out a world of “authentic Africa.” Of interest, in the location that is Lang’ata road, is how these clubs attempt to blend in with the history and landmarks. Along the road, there is a stadium, an airport, schools, a cemetery, two Universities, a military barrack, several malls, a game reserve, a women’s prison, and several housing estates. Lang’ata road is also a place of contests, buildings have been demolished as some land has been said to have been acquired illegally. The nervousness associated with ownership of land, and therefore possible forceful eviction, has affected the way some clubs are built. This has presented interesting opportunities for designers to create interiors that, while appreciating the impermanence of the clubs’ structures they provide illusions within these spaces where clients can “disappear” from threats of that outside world of contests. How design plays a role in creating new worlds that clients can disappear into and momentarily forget their woes is of interest in this paper.